A checklist of Poliosia Hampson, 1900 (Lepidoptera, Erebidae, Arctiinae) with emphasis on the Cambodian fauna, and the description of a new species to the genus - Bayarsaikhan, Ulziijargal; Na, Sol˗moon; Bae, Yang˗seop (Zootaxa, 2018)
A checklist of the genus Poliosia Hampson, 1900 is provided, along with a key for the Cambodian species, which includes the new species P. cardamomensis Bayarsaikhan & Bae, n. sp. Illustrations of adults and genitalia of all three Cambodian species are presented.